The study of Puffer Fish poisoning in children admitted in Pediatric department at Tishreen University Hospital in Lattakia 2015-2016 - صقور , سعاد محمد (Latakia University Journal -Medical Sciences Series, 2022)
Fish is one of the most delicious and healthiest dishes, but we should know that eating some species of fish threatens human health and life. The most dangerous of these species is the puffer fish, which contains tetrodotoxin that causes a range of symptoms such as dizziness, numbness, tingling in the mouth, and muscle weakness, and severe cases may appear with respiratory failure and death. This research presents four clinical cases who admitted to the Pediatric Department at Tishreen University Hospital in the years (2015-2016) with a diagnose of puffer fish poisoning: three males and one female, aged between (2-13) years. Symptoms in the majority of cases started with numbness and tingling around the mouth, and respiratory distress was the main problem in serious poisoning. Three children developed severe grade IV toxicity and required endotracheal intubation, and all were treated with neostigmine and intravenous atropine. One child died of respiratory failure, and the other three children were discharged without sequelae (48-72) hours after admission.